An application of asymmetric Toda–Yamamoto causality on exchange rate-inflation differentials in emerging economies - Umar, Mohammed; Dahalan, Jauhari (EconJournals, 2016)
The paper employs asymmetric causality test based on Toda and Yamamoto (1995) causality approach to further investigate the causal relationship between exchange rate and inflation differentials in Brunei, Malaysia and Singapore. We simulate critical values based on leverage bootstrapping and asymmetric causality test from the underlying empirical data.The results are compared among the Granger asymptotic Chi-square, the modified WALD leverage bootstrapped distributions and asymmetric causality test.The reported conflicting findings proved the existence of size distortion and nuisance parameter estimates when the traditional Granger approach is applied.The results from Toda–Yamamoto with asymmetric causality test establish the existence of Granger causality running from positive cumulative exchange rate shocks to positive cumulative shocks in inflation differentials for Brunei and Malaysia. However, the asymmetric causality for Singapore runs from both positive and negative cumulative domestic inflation shocks to positive and negative exchange rate shocks respectively. The policy implication of the findings is that a strong price stabilization policy during both good and bad times can stabilize exchange rate fluctuations in Singapore whereas; formulation of effective exchange rate policy can only achieve price stability in Brunei and Malaysia during good period.